Al-Dimoqratiyyah bidayah, al-dimoqratiyyah asas, al-dimoqratiyyah abadan : (Manshurat Al-Bayadir Al-Maghribiyyah, 1995)
'Democracy beginnings, democracy foundation, democracy forever : political framework for the new-left struggle and the hampered institutionalization' Politics.